Tumor necrosis Factor Receptor-1 (p55) deficiency attenuates tumor growth and intratumoral angiogenesis and stimulates CD8+ T cell function in melanoma - Rodriguez, Yamila Isabel (2020)
The role of tumor necrosis factor-α (TNF-α) in shaping the tumor microenvironment is ambiguous. Consistent with its uncertain role in melanoma, TNF-α plays a dual role, either acting as a cytotoxic cytokine or favoring a tumorigenic inflammatory microenvironment. TNF-α signals via two cognate receptors, namely TNFR1 (p55) and TNFR2 (p75), which mediate divergent biological activities. Here, we analyzed the impact of TNFR1 deficiency in tumor progression in the B16.F1 melanoma model. Tumors developed in mice lacking TNFR1 (TNFR1 knock-out; KO) were smaller and displayed lower proliferation compared to their wild type (WT) counterpart. Moreover, TNFR1 KO mice showed reduced tumor angiogenesis. Although no evidence of spontaneous metastases was observed, conditioned media obtained from TNFR1 KO tumors increased tumor cell migration. Whereas the analysis of tumor-associated immune cell infiltrates showed similar frequency of total and M2-polarized tumor-associated macrophages (TAMs), the percentage of CD8+ T cells was augmented in TNFR1 KO tumors. Indeed, functional ex vivo assays demonstrated that CD8+ T cells obtained from TNFR1KO mice displayed an increased cytotoxic function. Thus, lack of TNFR1 attenuates melanoma growth by modulating tumor cell proliferation, migration, angiogenesis and CD8+ T cell accumulation and activation, suggesting that interruption of TNF-TNFR1 signaling may contribute to control tumor burden.